Determinants of Village Financial System (Siskeudes) Quality in Wanasaba Sub-district - Agustina, Lia; Nurabiah, Nurabiah (East Asian Journal of Multidisciplinary Research, 2025)
This study aims to objectively examine the determinants of the quality of the village financial system (Siskeudes) at the village office in Wanasaba sub-district. This research addresses the gaps identified in previous research. This study uses a quantitative approach, Using purposive sampling method, with the criteria of selecting village officials involved with Siskeudes. Data were gathered through questionnaires distributed to respondents, employing a 5-point Likert scale. The research sample included 70 respondents who were directly engaged with Siskeudes, and data analysis was conducted using SmartPLS software. The results of this study show that organizational culture variables have a positive impact on the quality of village financial systems. However, no impact was found between training and user competence on the quality of village financial systems.